أبو عثمان المازني وجهوده اللغوية والنحوية (ممثِّلُ أهل النحو من مدرسة البصرة) - Sirfi Fatoni, Ahmad (Institut Kariman Wirayudha Sumenep, 2025)
This research deals about Abu Usman al-Mazini’s views and efforts on the construction of the grammar rule, as he is a representative grammarian from the Bashrah school, and this research is important to do in order to reveal a linguist who has a high contribution to the construction of the grammar rule. The type of this research is qualitative research using descriptive and critical analysis. The method of data collection is the al-istima’ method with note-taking technique. The findings are as follows: (1) Abu Usman al-Mazini is strict in taking the analogy and rejects what is not consistent with it from the Arab language and some readings of the Qur'an; (2) Sibawaih obliges i’rab al-raf’i of the word “الرجل” after “أيٌّ” in the al-nida’ as in: يا أيها الرجل, because the word